Executive Stock Ownership and Enterprise Digital Transformation: Interest Convergence or Trench Defense - Na Chen; Shuili Yang (Discrete Dynamics in Nature and Society)
Digital transformation gives enterprises new development momentum and vitality. The existing research studies mainly focused on the economic consequences of the digital transformation of enterprises, and few literatures pay close attention to the driving factors of digital transformation. In particular, they ignored the important role played by the core element of executives. To fill this gap, this study empirically examines the influence mechanism of executive ownership on enterprise digital transformation based on Chinese A-share manufacturing listed companies from 2008 to 2021. The results show that there is an inverted U-shaped relationship between executive ownership and enterprise digital transformation. When the shareholding ratio is low, “interest convergence” is dominant; when the shareholding ratio is high, “trench defense” is more obvious. Heterogeneity analysis shows that the nature of property rights and the degree of industry competition can alleviate the threshold effect of executive ownership on digital transformation, while ownership concentration will aggravate the threshold effect of executive ownership on digital transformation. This study not only enriches the research on the influencing factors of digital transformation but also provides practical guidance for enterprises to improve the design of incentive mechanism and promote the digital transformation of enterprises.